Mediation Of Tanjung Priok Port Workers' Conflict With Communication Strategy (Case Study PT. Temas Port Temas Jakarta) - Muhammad Saiful Islam (International journal of technology and education research, 2025)
Labor wage issues often lead to industrial disputes that can disrupt operational stability in companies, including in the maritime logistics sector. PT Temas, a company engaged in sea transportation, faced a labor wage conflict that required effective communication strategies to resolve. This study aims to analyze the public relations communication strategy used by PT Temas as a means of mediating wage-related labor conflicts. Using a qualitative case study approach, the research reveals that transparent communication, involvement of labor representatives, and consistent dissemination of company policies were essential in reducing tensions and reaching a resolution. The findings indicate that public relations communication strategies play a vital role in conflict mediation, ensuring not only the continuity of operations but also improving industrial relations within the company.